Strategi Komunikasi Interpersonal Karyawan dalam Meningkatkan Loyalitas Pelanggan di Allea Outfit Pekanbaru - Charen Monicha; Yantos Yantos (Al-Manar Journal of Accountancy and Business Studies, 2026)
This study aims to examine and analyze the interpersonal communication strategies employed by employees in enhancing customer loyalty. This research adopts a qualitative approach with a descriptive research design. The informants in this study consist of one manager, two employees, and five customers who are registered members. Data collection techniques include observation, in-depth interviews, and documentation. Data analysis is carried out through the stages of data reduction, data display, and conclusion drawing, using triangulation techniques to ensure the validity of the data. The results show that employees implement interpersonal communication strategies consisting of openness, empathy, supportiveness, positiveness, and equality. The aspect of openness is reflected in the delivery of honest and transparent information to customers. Empathy is demonstrated through employees’ ability to understand customers’ feelings and needs, as well as to handle complaints appropriately. Supportiveness is manifested through providing recommendations and alternative products that suit customers’ needs. Positiveness is shown through creating a good first impression, maintaining friendliness and politeness, and the ability to deal with various customer characteristics. Meanwhile, equality is reflected in providing fair and non-discriminatory service to all customers.